EMPLOYEE WELL-BEING IN THE DIGITAL ERA: BALANCING TECHNOLOGY AND MENTAL HEALTH IN THE WORKPLACE - Eli Retnowati; Fahmi Kamal; Karyono Karyono; Tri Seno Anjanarko; Klemens Mere (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The digital era has transformed the workplace, introducing new opportunities and challenges for employee well-being. This article explores the impact of technology on mental health in the workplace, focusing on strategies to balance productivity and well-being. Through a literature review of studies published from 2020 onwards, the article examines key themes such as digital overload, remote work challenges, and the role of organizational support in promoting mental health. The findings reveal that while technology enhances efficiency, it also contributes to stress and burnout if not managed effectively. Practical recommendations are provided to help organizations foster a healthy work environment, including the implementation of digital wellness programs, flexible work policies, and mental health resources. This study contributes to the growing body of literature by synthesizing contemporary research and offering actionable insights for improving employee well-being in the digital age.